Use of panel testing for detection of antinuclear antibody in a resource-limited setting: an appraisal. Issue 8 (16th November 2016) - Minz, Ranjana Walker; Kumar, Yashwant; Saikia, Biman; Anand, Shashi; Varma, Subhash; Singh, Surjit
ABSTRACT: Objectives : Despite an increase in the incidence of systemic connective tissue diseases (CTD), panel testing for detection of antinuclear antibodies (ANA) is not a routine practice in many health centers of the Indian subcontinent. Consequently, the data on its significance is scanty. Methods : To evaluate utility of panel testing, line immunoassay (LIA) and indirect immunofluorescence antinuclear antibody test (IIF-ANA) were performed in 321 cases of CTD. Results : Out of 321 serum samples screened by the above tests, 227 were positive and 18 were negative by both LIA and IIF-ANA. Additional 11/321 (3.4%) cases were picked up by LIA. SSA was most common specificity in these cases followed by SSA/SSB, SSB, Ro-52, Jo-1, dsDNA and nRNP/Sm. Conclusion : Use of LIA along with IF-ANA and ELISA improves sensitivity of CTD screening.